2022
DOI: 10.3390/ijms232214328
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenon E Effects on Gene Expression in PC-3 Prostate Cancer Cells

Abstract: Polyphenon E (Poly E) is a standardized, caffeine-free green tea extract with defined polyphenol content. Poly E is reported to confer chemoprotective activity against prostate cancer (PCa) progression in the TRAMP model of human PCa, and has shown limited activity against human PCa in human trials. The molecular mechanisms of the observed Poly E chemopreventive activity against PCa are not fully understood. We hypothesized that Poly E treatment of PCa cells induces gene expression changes, which could underpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…However, the active compounds of prostate chemo-preventative effects are not yet known. The presence of saccharide fatty acid esters [276,277], asperulosidic acid [277], and the anthraquinone damnacanthal [278] in the fruits, as well as the rich content of epicatechin and escopoletin in the leaves (Figure 6), may contribute to the cytotoxic effects of its extracts in several types of cancer cells including PC3 [279][280][281][282][283]. A recent review of 51 clinical and preclinical studies showed promising antitumor, antiproliferative, pro-apoptotic, antiangiogenesis, antimigratory, anti-inflammatory, and immunomodulatory activities [275].…”
Section: Morinda Citrifolia Lmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the active compounds of prostate chemo-preventative effects are not yet known. The presence of saccharide fatty acid esters [276,277], asperulosidic acid [277], and the anthraquinone damnacanthal [278] in the fruits, as well as the rich content of epicatechin and escopoletin in the leaves (Figure 6), may contribute to the cytotoxic effects of its extracts in several types of cancer cells including PC3 [279][280][281][282][283]. A recent review of 51 clinical and preclinical studies showed promising antitumor, antiproliferative, pro-apoptotic, antiangiogenesis, antimigratory, anti-inflammatory, and immunomodulatory activities [275].…”
Section: Morinda Citrifolia Lmentioning
confidence: 99%
“…However, more studies must be performed to establish if this natural product can be translated into any anticancer intervention. may contribute to the cytotoxic effects of its extracts in several types of cancer cells including PC3 [279][280][281][282][283]. A recent review of 51 clinical and preclinical studies showed promising antitumor, antiproliferative, pro-apoptotic, antiangiogenesis, antimigratory, anti-inflammatory, and immunomodulatory activities [275].…”
Section: Morinda Citrifolia Lmentioning
confidence: 99%